Intravenous delivery of a liposomal formulation of voriconazole improves drug pharmacokinetics, tissue distribution, and enhances antifungal activity - Danillo F. M. C. Veloso; Naiara I. G. M. Benedetti; Renato I. Ávila; Thiago S. A. Bastos; Thaísa C. Silva; Maria R. R. Silva; Aline C. Batista; Marize C. Valadares; Eliana M. Lima (Taylor & Francis Group, 2018)
Voriconazole (VCZ), a triazole with a large spectrum of action is one of the most recommended antifungal agents as the first line therapy against several clinically important systemic fungal infections, including those by Candida albicans. This antifungal has moderate water solubility and exhibits a nonlinear pharmacokinetic (PK) profile. By entrapping VCZ into liposomes, it is possible to circumvent certain downsides of the currently available product such as a reduction in the rate of its metabolization into an inactive form, avoidance of the toxicity of the sulfobutyl ether-beta-cyclodextrin (SBECD), vehicle used to increase its solubility. PKs and biodistribution of VCZ modified by encapsulation into liposomes resulted in improved antifungal activity, due to increased specificity and tissue penetration. In this work, liposomal VCZ resulted in AUC0-24/MIC ratio of 53.51 ± 11.12, whereas VFEND® resulted in a 2.5-fold lower AUC0-24/MIC ratio (21.51 ± 2.88), indicating favorable antimicrobial systemic activity. VCZ accumulation in the liver and kidneys was significantly higher when the liposomal form was used. Protection of the drug from biological degradation and reduced rate of metabolism leads to a 30% reduction of AUC of the inactive metabolite voriconazole-N-oxide (VNO) when the liposomal drug was administered. Liposomal VCZ presents an alternative therapeutic platform, leading to a safe and effective treatment against systemic fungal infections.